Fish‐Microarray: A Miniaturized Platform for Single‐Embryo High‐Throughput Screenings. (28th November 2017) - Popova, Anna A.; Marcato, Daniel; Peravali, Ravindra; Wehl, Ilona; Schepers, Ute; Levkin, Pavel A.
Abstract: Small molecule high‐throughput screenings are essential for the fields of drug discovery and toxicology. Such screenings performed on whole animals are more physiologically relevant leading to more predictive results. However, due to challenges in automation, high costs and absence of miniaturized solutions for animal‐based experiments, high throughput screenings based on animal models are still in its infancy. Here a platform for miniaturized high throughput whole‐organism screenings is presented. The new platform is based on patterns of hydrophilic spots separated by superhydrophobic borders. The difference in wettability of spots and borders generates the effect of discontinuous dewetting and allows for formation of arrays of microdroplets that incorporate single fish embryos. Due to the flat border‐less nature of the platform, the system is compatible with single‐step collection of embryos and pipetting‐free parallel addition of chemical libraries using the "sandwiching method." The system is miniaturized and allows for incubation of embryos in volumes as low as 5 µL. Finally, the platform realizes surface tension based immobilization of single embryos inside of each microcompartment and permits high‐throughput microscopic analysis directly on the platform. Thus, this method combines the advantages of microarrays, such as high‐throughput and simplicity, with the power of in vivo experiments. Abstract : A platform for miniaturized high‐throughput whole‐organism screenings is presented. The Droplet‐Microarray platform is based on patterns of hydrophilic spots separated by superhydrophobic regions and allows for spontaneous formation of arrays of microdroplets incorporating single zebrafish embryos. The system allows for compound screening of embryos in volumes as low as 5 µL and microscopic analysis directly on the platform.